Technical Status and Development Trend of Medical Electron Linear Accelerators - Zhiqiang ZHU; Peng CHENG; Liuli CHEN; Pengcheng LONG; Leiming SHANG; Tao HE; Liqin HU; Consortium FDS (Zhongguo yiliao qixie zazhi)
More than 70% of tumor patients require radiotherapy. Medical electron linear accelerators are important high-end radiotherapy equipment for tumor radiotherapy. With the application of artificial intelligence technology in medical electron linear accelerator, radiotherapy has evolved from ordinary radiotherapy to today’s intelligent radiotherapy. This study introduces the development history, working principles and system composition of medical electron linear accelerators. It outlines the key technologies for improving the performance of medical linear electron accelerators, including beam control, multi-leaf collimator, guiding technology and dose evaluation. It also looks forward to the development trend of major radiotherapy technologies, such as biological guided radiotherapy, FLASH radiotherapy and intelligent radiotherapy, which provides references for the development of medical electron linear accelerators.